2004
DOI: 10.1111/j.1440-1746.2004.03444.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiologic analysis of hepatitis C virus infection in injecting drug users with acute hepatitis C in Japan

Abstract: Hepatitis C virus of the non-1b subtype, particularly subtype 2b, seemed to be transmitted between IDUs very recently in Yamaguchi prefecture, Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Possible transmission routes that were assessed by interviewing each patient were compared between those with genotype 1 and those with non-1 genotypes. As shown in figure 2 , the major transmission routes appeared to be different between the 2 types: intravenous drug abuse was the major route of non-1 genotype HCV transmission, which is consistent with the results of previous reports [15,16] . The sustained virological response rates in these patients, 72% for genotype 1 and 95% for non-1 genotype, are better than those in previous reports, probably due to the shorter duration of infection (associated with less advanced disease) and younger age, both of which are factors associated with favorable outcomes of IFN therapy [17,18] .…”
Section: Features Of Recent Hcv Transmission In Japansupporting
confidence: 90%
See 1 more Smart Citation
“…Possible transmission routes that were assessed by interviewing each patient were compared between those with genotype 1 and those with non-1 genotypes. As shown in figure 2 , the major transmission routes appeared to be different between the 2 types: intravenous drug abuse was the major route of non-1 genotype HCV transmission, which is consistent with the results of previous reports [15,16] . The sustained virological response rates in these patients, 72% for genotype 1 and 95% for non-1 genotype, are better than those in previous reports, probably due to the shorter duration of infection (associated with less advanced disease) and younger age, both of which are factors associated with favorable outcomes of IFN therapy [17,18] .…”
Section: Features Of Recent Hcv Transmission In Japansupporting
confidence: 90%
“…Therefore, intravenous drug abuse has become an important route of HCV transmission among young people [8,14] . Satoh et al [15] investigated the HCV genotypes that are spreading among Japanese IDUs and found that non-1b genotypes of HCV, particularly genotype 2b, seemed to be most prevalent among IDUs. We also examined the HCV genotypes in 42 young (less than 40 years old) chronic hepatitis patients with HCV who were treated by peginterferon and ribavirin combination therapy at the Kinki University Hospital between 2006 and 2008.…”
Section: Features Of Recent Hcv Transmission In Japanmentioning
confidence: 99%
“…Genotype 2 HCV accounts for approximately 25%‐30% of chronic HCV infections in Japan, and there is evidence this percentage is higher among persons younger than 40 years and those who inject drugs . Maternal transmission of HCV has increased significantly in Japan in the last decade, and HCV genotype 2 is now the most prevalent HCV genotype in Japanese children less than 17 years old …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that HCV‐2 or 3, but not HCV‐1, was prevalent among PWID in the main islands of Japan . These data suggest that HCV‐2/3 infection occurred by another distribution channel of illegal drugs in the main islands of Japan.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, we speculate that IDU might have been the driving Previous studies reported that HCV-2 or 3, but not HCV-1, was prevalent among PWID in the main islands of Japan. [40][41][42][43][44] These data Although the MSM population was not included in our study, it has been reported that the number of HIV cases among MSM has increased in Okinawa. 48 The HCV transmission network among MSM is international 45,49,50 and MSM tourists visit Okinawa from other areas in Japan or overseas.…”
Section: Discussionmentioning
confidence: 92%